An atom economical method for the direct synthesis of quinoline derivatives from substituted o-nitrotoluenes. Issue 14 (13th January 2015) - Liu, Guiyan; Yi, Maocong; Liu, Lu; Wang, Jingjing; Wang, Jianhui
Abstract : A one-pot procedure for the preparation of substituted quinolines from substituted o -nitrotoluenes with electron-withdrawing groups and olefins (acrylic esters and acrylonitriles) using a cesium catalyst under mild reaction conditions is reported. The process involves a [2+4] cycloaddition mechanism. Abstract : A highly efficient one-pot procedure for the preparation of substituted quinolines from substituted o -nitrotoluenes with electron-withdrawing groups and olefins (acrylic esters and acrylonitriles) using a cesium catalyst has been developed. A plausible [2+4] cycloaddition mechanism is proposed. This method uses nitroaromatic compounds as the starting materials to give quinoline derivatives in good to high yields under mild conditions with no transition metal catalysis. It provides an atom economical pathway for the synthesis of quinoline derivatives which could be used in industrial processes.